Identificación de minadores (Diptera: Agomyzidae) asociados con hortalizas, y sus parasitoides. - García-Palacios, Daniel; Martínez, Néstor; Valdez Carrasco, Jorge Manuel (Instituto de Ecología, A.C., 2014)
Leaf-miners species present in the production zone of vegetable crops of the states of Morelos, Puebla, and Veracruz were studied. 360 flies and 390 parasitoids were collected. The following leaf-miner species were identified: Liriomyza trifolii (Burgess 1880) and Liriomyza sativae Blanchard 1938. Three parasitoid species were identified Neochrysocharis sp., Opius dissitus Muesebeck and Closterocerus cinctipennis Ashmead.